2009
DOI: 10.1002/eqe.934
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐active tuned mass damper building systems: Design

Abstract: SUMMARYPassive and Semi-Active Tuned Mass Damper (PTMD and SATMD) building systems are proposed to mitigate structural response due to seismic loads. The structure's upper portion self plays a role either as a tuned mass passive damper or a semi-active resetable device is adopted as a control feature for the PTMD, creating a SATMD system. Twodegree-of-freedom (2-DOF) analytical studies are employed to design the prototype structural system, specify its element characteristics and effectiveness for seismic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…For a given structural configuration, the connections between the segregated (upper) structure and main (lower) structure can be semi-active resetable device for a 12-story SATMD building system, and the design of resetable device is based on the previous results of the system design [17]. For these cases, the maximum device forces are set at 644kN and 1,573kN, which represent the value of 13.8% [26] of the structural weight multiplied by mass ratios of 0.244 (10+2) and 0.594 (8+4), respectively.…”
Section: Dynamic Characteristics Of Resetable Devicementioning
confidence: 99%
See 1 more Smart Citation
“…For a given structural configuration, the connections between the segregated (upper) structure and main (lower) structure can be semi-active resetable device for a 12-story SATMD building system, and the design of resetable device is based on the previous results of the system design [17]. For these cases, the maximum device forces are set at 644kN and 1,573kN, which represent the value of 13.8% [26] of the structural weight multiplied by mass ratios of 0.244 (10+2) and 0.594 (8+4), respectively.…”
Section: Dynamic Characteristics Of Resetable Devicementioning
confidence: 99%
“…As a separate part of the present research, simplified PTMD and SATMD building models were presented and implemented in a system design simulation [17]. In the trade-off parametric study of this approach, the efficiency of spreading stiffness between resetable devices and rubber bearings was illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the authors of this study suggested the TMD principle-based design of the "TMD (passive and semiactive) building systems" and its seismic performances were evaluated over three probabilistically scaled suites of earthquake records parameters [16][17][18]. The results showed that the suggested TMD modified systems provide more effective and robust response mitigation over a range of ground motions within each earthquake suite.…”
Section: Introductionmentioning
confidence: 94%
“…The design parameters for the smart isolation layer are basically based on and derived from the previous linear design and application studies [16][17][18]. For example, the tuning ratio for this multi-degree-of freedom (MDOF) system is nearly equal to the tuning ratio for a two-degreeof freedom (2-DOF) system for a mass ratio of μΦ, where Φ is the amplitude of the first mode of vibration for a unit modal participation factor computed at the location of the upper isolated stories.…”
Section: Design Of the Isolation Layermentioning
confidence: 99%
“…"|tQH Qo = Q}t w xR=U pt=W |O= R; |xHQO wO |xv=t=U "1 pmW [12] "Ov=xOW xO=iDU= xRQru}tR Q@=Q@ QO =yxR=U p=ai pQDvm xR=U pQDvm x@ u=vJty 'ODi}@ Q=m R= sy lQLt Qo = |DL 'OQ=O p=aiQ}e w p=ai <= RH= [13] "OQm Oy=wN |v=}=W ltm O}=@ 'OQ}o Q= Qk xO=iDU= OQwt xR=U CmQL Vy=m |= Q@ 'p=ai pQDvm |xv=t=U Qo = QO QwmPt |xv=t=U uOW|}= QH= R= 'lQLt u=wD C}OwOLt "OwW O}rwD |oQR@ |wQ}v p=ai |xv=oOvJ |tQH |=yQo= Q}t 'wQ u}= R= "Ovm|t |Q}owrH |ak=w |=yu=tDN=U uQ=kDt=v |=yxR=U |= Q@ p=ai |xv=oOvJ |tQH |=yQo= Q}t OQmrta w [14] '|iQat 'p=ai |xv=oOvJ |tQH |=yQo= Q}t |wQ Q@ |D=ar=]t u}vJty [15] "CU= xOW |UQQ@ [16] "CU= xOW s=Hv= xR=U w l=N VvmQOv= [17] "CU= xDiQo Q= Qk |UQQ@ OQwt Q}eDt |DNU =@ p=aixt}v |tQH l} R= u; QO xm 'CU= xOW |iQat 2010 p=U QO p=aixt}v |tQH |=yQo= Q}t R= [18] "CU= xOW xO=iDU= xR=U |SQv= hqD= |xr}Uw u=wvax@ lQLDt x=ox}mD =@ Qvi = Q wQ}v Q=OQ@ u=wD|t 'OW=@ u}tR CmQL CLD xR=U Qo [22] "OvDUy |]N ?=DW w u}ov=}t Q=O}=B 9 |x]@= Q <= R= x@ lQ=tw}v VwQ [23] "CU= xOW xO=iDU= 'CU= Qo}O VwQ [22] %CU= [23] "lQ=tw}v VwQ "1 pwOH…”
mentioning
confidence: 99%